Essentials of physical pharmacy - Aggarwal, Sanjive (New Delhi, India : Anmol Publications, 2010)
This book is a modest attempt to provide a simple mathematical text for those who desire to equip themselves with a knowledge of the statistical methods used in modern times.
Biological molecules -- Atomic force microscope -- Biological applications of AFM -- Thermodynamics interactions -- Thermodynamic parameters of lactoglobulin -- Fundamentals of enzyme kinetics -- Enzyme inhibition -- Mass spectrometry -- Tandem mass spectrometry -- The importance of conjugation
Includes index.
Keywords: CHEMISTRY, PHYSICAL AND THEORETICAL